Conducting research in sports engineering education - Frank, B.; Donnelly, C. (Sports Engineering, 2018)
This aim of this paper is to provide recommendations for developing sports engineering education research (SEER) both at the individual and community levels. The emergence of this field can be positively informed by reflection on similar developments in other fields, particularly engineering education and health science education research. The large traditional engineering disciplines, including chemical, electrical and computer, and mechanical, have well-developed communities and publication venues for educational research. Health professions, including kinesiology, rehabilitation, nursing, and medicine, have allied with sports engineering to develop educational research that can inform methods and provide opportunities for dissemination. As an interdisciplinary field, it is also critical to draw on the growing body of interprofessional education research. The rich literature relating to discipline-based educational research (DBER) and the Scholarship of Teaching and Learning (SoTL) can support individuals moving into this field, and observations by communities in other disciplines can provide guideposts for sports engineering. There are well-established processes and methodologies that can be adapted from other discipline-based educational research fields. As stand-alone sports engineering education programs are relatively rare and young, there is an opportunity available to create a culture that values research on education in the field.